Pengukuhan Institusi Keluarga Melalui Kawalan Terhadap Perceraian: Analisis Literatur - Mohd Saad, Ahmad Hariri; Hj Azahari, Raihanah (Jurnal Fiqh, 2014)
The family institution is one of the basic principles in developing a community. The success and failure of the community largely depends on the family institution. A solid family institution ensures the development of a healthy community. A lot of research has been conducted that discussed the family institution and marriage in the form of dissertation writings, thesis, books or journal articles. There are also non-academic writings that discussed this matter, such as books and popular articles. Thus, this journal will look at the literature that discusses the ways to strengthen marriage through the prevention of divorce. The literature that was being reviewed in this journal tended to focus on the prediction of the outcome of a marriage or relationships in marriage rather than the process of developing the marriage. The review also showed that most of the researchers tend to put too much focus on identifying how a split in the marriage could happen. As an alternative, this research needs to be done in order to identify the strengths in the family structure and units.